2019
DOI: 10.1192/bjb.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry in intellectual disability psychiatry: literature review

Abstract: Aims and MethodThe aims of this review were to explore the effectiveness and patient and provider acceptability of telepsychiatry consultations in intellectual disability, contrasting this with direct face-to-face consultations and proposing avenues for further research and innovation. Computerised searches of databases including AMED and EMBASE were conducted.ResultsFour USA studies of intellectual disability telepsychiatry services have been reported. The majority (75%) focused on children with intellectual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
(44 reference statements)
1
12
0
1
Order By: Relevance
“…So, the current situation provides valuable insights into relevant aspects for delivering eHealth interventions to people with intellectual disabilities directly. In a review of telepsychiatry among people with intellectual disabilities in a psychiatric setting, Madhavan ( 2019 ) concluded that it constituted an effective means through which to empower people with intellectual disabilities, while, simultaneously, reducing costs.…”
Section: Discussionmentioning
confidence: 99%
“…So, the current situation provides valuable insights into relevant aspects for delivering eHealth interventions to people with intellectual disabilities directly. In a review of telepsychiatry among people with intellectual disabilities in a psychiatric setting, Madhavan ( 2019 ) concluded that it constituted an effective means through which to empower people with intellectual disabilities, while, simultaneously, reducing costs.…”
Section: Discussionmentioning
confidence: 99%
“…These studies present several limitations: terms like “telemedicine”, “telehealth” and “e-health” are often used interchangeably for a broad range of support services and technologies, different aims and interventions, small sample size and different type of selection procedure, different age range of patients, poor protocols for a randomized controlled trial, compliance level of parents or caregivers, different use of the assistive products, different internet broadband services. It is therefore difficult to draw firm conclusions about the benefits and limitations of such a modality in people with intellectual disabilities [ 52 , 53 ].…”
Section: Limitations Of Studies On the Use Of Telemedicine In Peopmentioning
confidence: 99%
“…La aplicación de telemedicina de forma generalizada precisa atención a las barreras en la legislación en lo que se refiere a los estándares de accesibilidad y los plazos recogidos en estas legislaciones para implementarlos (Annaswamy et al, 2020). En Reino Unido, por ejemplo, se ha incluido en algunos planes de salud para las personas con discapacidad intelectual en el proceso de envejecimiento, que la telemedicina solo será un com-plemento a las consultas presenciales y en ningún caso sustituirá a estas (Madhavan, 2019).…”
Section: Telemedicina Y Discapacidad: Tendencias Y Retosunclassified